Calculation of electric field strengths at a sharp edge - Brailsford, David F.; Robertson, Andrew J. B. (Elsevier, 1968)
Sharp edges were first used for field ionisation mass spectrometry by Beckey. Although Cross and Robertson found that etched metal foils were more effective than razor blades for field ionisation, blades are very convenient for determination of field ionisation mass spectra, as reported by Robertson and Viney. The electric field at the vertex of a sharp edge can be calculated by the method of the conformal transformation. Here we give some equations for the field deduced with the assumption that the edge surface can be approximated by a hyperbola. We also compare two hyperbolae with radii of curvature at the vertex of 500 Angstrom and 1000 Angstrom with the profile of a commercial carbon-steel razor blade.